Historiography of the policy of violence in the introduction of the Soviet model to the higher education system of Uzbekistan (part 3) - Imamov Ulug'bek Ismailovich (Genius Journals, 2023)
During the totalitarian regime in Uzbekistan SSR, it was impossible to create a true history of Uzbekistan, the scope of studying problems and their sources was strictly limited, it was impossible to give a true assessment of historical events, and a dogmatic approach prevailed. After the establishment of the Soviet government in Turkestan, the colonial government took full control over the education system of the local people. It is stated in this article that studying the historiography of the Soviet policy of violence carried out in the field of education in this period, its consequences affecting the educational system, comparative analysis, drawing objective conclusions from them is one of the urgent tasks of the history of Uzbekistan
Keywords: Soviet totalitarianism; knowledge spillovers; cultural revolution